2012
DOI: 10.1111/j.1755-3768.2011.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive antibiotics in the treatment of acute bacterial endophthalmitis following cataract surgery

Abstract: establishing the efficacy and safety of using injectable, shape-memory alloy clips to fixate scleral buckling hardware. The technique is technically simpler and faster than tying conventional suture, and the clips are several times stronger than conventional suture. Further testing is underway to determine the stability, biocompatibility and surgical utility of these injectable shape-memory clips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The EVS also did not evaluate the role of antibiotics administered orally (Barry et al 2013). In 2012, Hoper et al compared the use of oral ciprofloxacin versus moxifloxacin in PE treatment and showed that adjunctive oral moxifloxacin may decrease the need for repeated intravitreal injections of antibiotics and improve clinical outcome (Hooper et al 2012). Also, levofloxacin has been shown to have broad spectrum of activity against Gram-positives and to achieve effective intravitreal levels after oral administration; thus, it can be a potential adjunctive antibiotic in PE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The EVS also did not evaluate the role of antibiotics administered orally (Barry et al 2013). In 2012, Hoper et al compared the use of oral ciprofloxacin versus moxifloxacin in PE treatment and showed that adjunctive oral moxifloxacin may decrease the need for repeated intravitreal injections of antibiotics and improve clinical outcome (Hooper et al 2012). Also, levofloxacin has been shown to have broad spectrum of activity against Gram-positives and to achieve effective intravitreal levels after oral administration; thus, it can be a potential adjunctive antibiotic in PE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comparison of the PE risk between this study and other studies is only meaningful if the other studies have implemented the use of intracameral antibiotics as these are known to decrease the PE risk (Montan et al 2002;ESCRS Endophthalmitis Study Group 2007;Lundstrom et al 2007;Garat et al 2009;Friling et al 2013;Shorstein et al 2013). The use of systemic antibiotics in the treatment of PE is debated (Hooper et al 2012) and so is the use of postoperative topical antibiotics. The cases of PE in this study were treated either with or without systemic antibiotics and most of the cases received a mixture of topical corticosteroids and antibiotics postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…The use of systemic antibiotics in the treatment of PE is debated (Hooper et al. ) and so is the use of postoperative topical antibiotics. The cases of PE in this study were treated either with or without systemic antibiotics and most of the cases received a mixture of topical corticosteroids and antibiotics postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding has been questioned because of the exclusion of patients with severe endophthalmitis and the choice of adjunctive antibiotics: ceftazidime has poor activity against the dominant Gram-positive organisms and amikacin has very limited intraocular penetration. Since then, only small studies have evaluated the efficacy of systemic antibiotic therapy in endophthalmitis with varying methodologies and results [12][13].…”
Section: The Role Of Systemic Antibioticsmentioning
confidence: 99%